DAMPAK PEMALSUAN DATA IDENTITAS ADMINISTRASI PENIKAHAN TERHADAP STATUS HUKUM PERNIKAHAN INDONESIA DAN PERSPEKTIF HUKUM ISLAM - Ahmad Dailami; Rumba Triana; Arijulmanan Arijulmanan (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2018)
Marriage is the Islamic Shari'ah, where Allah SWT has made this Shari'a to create the goal of sakinah, mawaddah, rahmah. The Indonesian government considers it very important about marriage and therefore national marriage legislation is enacted. So issued law No. 1 of 1974 on marriage and government regulation No. 9 of 1975 on the implementation of law No. 1 of 1974 which regulates the problem of marriage. And to keep the destination of this marriage then the government ordered the public to record every marriage that took place in the Ministry of Religious Affairs through the Office of Religious Affairs (KUA) located in the District. As stipulated in the Compilation of Islamic Law article 2 concerning Marriage Registration is "recording of marriage of those who hold their marriage according to Islamic religion, performed by the appointing officer as meant in Law Number 32 Year 1954 concerning Recording of Marriage, Divorce and Reconciliation. But even so unregistered marriages are still considered valid by marriage law in Indonesia, and can be canceled with a 3rd party lawsuit, as for Islamic law marriages that take place without recording can not be undone.Keywords: Marriage, Identity Data Fraud